PENGATURAN PEMBUKTIAN TERBALIK TERBALIK DALAM UNDANG-UNDANG KORUPSI - Eka Artajaya, I Wayan (Jurnal Ilmiah Raad Kertha, 2024)
The criminal act of corruption not only harms state finances, but also constitutes a violation of the social and economic rights of society at large, so that the criminal act of corruption needs to be classified as a crime whose eradication must be carried out in an extraordinary manner, to further guarantee legal certainty, avoid diversity of legal interpretations and providing protection for the social and economic rights of the community, as well as fair treatment in eradicating criminal acts of corruption. The statutory regulations that regulate criminal acts of corruption are Law no. 28 of 1999 concerning the Administration of a State that is Clean and Free from KKN, Law no. 31 of 1999 in conjunction with Law no. 20 of 2001 concerning Eradication of Corruption Crimes, Law no. 30 of 2002 concerning the Corruption Eradication Commission, and finally with the ratification of the United Nations Convention Against Corruption, 2003 (United Nations Convention Against Corruption, 2003) through Law no. 7 of 2006. The theories used to support the preparation of this book are the Theory of the Rule of Law, the Hierarchy Theory of Legal Norms, the Theory of Authority, the Concept of Corruption and Corruption Crimes and the Concept of Reverse Evidence. The approaches used in preparing this book are: statutory approach, conceptual research approach, case approach. Legal Materials use primary legal materials, in the form of secondary law and other legal materials. Primary legal materials include court decisions that have permanent legal force and laws related to corruption. Secondary legal materials are books, unpublished scientific works, journals and newspapers. Other legal materials are internet sites regulating the reverse evidence system in the provisions of Article 12B of Law Number 20 of 2001, Articles 37, 37A and 38B of Law Number 31 of 1999 in conjunction with Law No. 20 of 2001 and the Criminal Procedure Code. is limited or balanced, and uses a negative proof system according to law (negatief wettelijk overtuiging). The Public Prosecutor is still obliged to prove his charges. In the future, it is necessary to carry out an evaluation of the regulation of Corruption Crimes, it is necessary to strictly regulate the substance of the legal system of reverse evidence so that its application can be implemented effectively and is not just a rule contained in the norms.